Model Setting of Political Party System and Electoral Systems to Prevent Political Corruption - Agus Riwanto; Achmad Achmad (Jurnal Cita Hukum, 2018)
Abstract. This study aims to analyze and examine the causes of political parties to systemic corruption and efforts to save them from corruption. Political parties are important actors in democracy in a country. Democracy manifests in the form of election, the main actor of the election is a political party. If the main actor of corruption is confirmed, democracy and elections will fall. The result is a bad stigma in political parties: democracy yes political party no. Based on the research result that the cause of political party of corruption: First, the placement of political party as an important agent in state structure of Indonesia Post-amendment of 1945 Constitution, but it is not balanced with recruitment model of political party cadre that meritokratic, integrity and, responsibility to the public. Secondly, financing for running the organization of political parties is very expensive, especially if the political parties are projected to win the seats of DPR / D, governor/regent/mayor and president. Third, the choice of model of legislative election system in 2009 and 2014 based on Law Number 10 Year 2008 and Law Number 12 the Year 2012 on General Election of DPR, DPD, and DPRD (Indonesian Legislative Election) members are the most open-based voting proportional system. The recommendations for reforms to save political parties from corruption through party system and election system aspects are (1) to improve the recruitment model of political party cadre; (2) making alternative for financing model of political party organization; (3) tightening the requirements of political parties into election participants; (4) eliciting election costs by returning to open proportional systems with sequence numbers, and (5) designing alternative mixed-model electoral systems.Keywords: Arrangements, models, political parties, general elections and political corruptionAbstrakPenelitian ini bertujuan untuk menganalisis dan mengkaji tentang penyebab partai politik (parpol) melakukan korupsi sistemik dan upaya menyelamatkannya dari korupsi. Parpol adalah aktor penting dalam demokrasi di sebuah negara. Demokrasi terwujud dalam bentuk pemilu, aktor utama pemilu adalah parpol. Jika aktor utamanya korupsi dipastikan demokrasi dan pemilunya terpuruk. Akibatnya muncul stigma buruk pada parpol: demokrasi yes parpol no. Penelitian ini merupakan penelitian hukum empirisis (sosiologis) yang bersifat diskriptif-eksplanatoris. Karena penelitian ini adalah penelitian kualitatif, maka cara memperoleh data dilakukan dengan studi pustaka dan observasi. Teori yang digunakan adalah teori korupsi politik, teori sistem kepartaian dan teori sistem pemilu. Berdasarkan hasil penelitian bahwa penyebab parpol korupsi: Pertama, ditempatkannya parpol sebagai agen penting bernegara dalam struktur ketatanegaraan Indonesia Pascaamandemen UUD 1945, namun tidak diimbangi dengan model rekruitmen kader parpol yang meritokratis, berintegritas dan tanggungjawab pada publik. Kedua, pembiayaan menjalankan roda organisasi parpol sangat mahal, apalagi jika parpol diproyeksikan untuk meraih kursi DPR/D, gubernur/bupati/walikota dan presiden. Ketiga, pilihan model sistem pemilu legislatif tahun 2009 dan 2014 berdasarkan UU No.10/2008 dan UU No.12/2012 Tentang Pemilu Anggota DPR, DPD dan DPRD adalah sistem proporsional terbuka berbasis suara terbanyak. Adapun rekomendasi untuk reformasi menyelamatkan parpol dari korupsi melalui aspek sistem kepartaian dan sistem pemilu adalah, (1) memperbaiki model rekruitmen kader parpol; (2) membuat alternatif model pembiayaan organisasi parpol; (3) memperketat syarat parpol menjadi peserta pemilu; (4) mempermurah biaya pemilu dengan kembali ke sistem proporsional terbuka dengan nomor urut, dan (5) merancang alternatif sistem pemilu model campuran.Kata Kunci: Pengaturan, model, parpol, pemilu dan korupsi politik